2021
DOI: 10.3390/ma14164685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO2 Content on Microstructure and Properties of SiCp/Al-Si Composites Prepared by Powder Metallurgy

Abstract: The effect of CeO2 content on the microstructure and properties of SiCp/Al-Si composites prepared by powder metallurgy was studied, and the mechanism of CeO2 in composites was deeply analyzed. The results show that the addition of the appropriate amount of CeO2 can refine the Si particles and improve the tensile properties of the SiCp/Al-Si composites. As the CeO2 content increases from 0 to 0.4 vol%, the particle size of the Si phase shows a tendency to decrease first and then increase, while the tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…During the solidification process in cast composites, TiB 2 elements cause increase in the dislocation of density [33][34][35][36]. Xuedan Dong et al [10] observed that, when the CeO 2 content was increased, the mechanical properties of the composites were enhanced. Since, Stircasting technique is adopted for the purpose of fabrication of composites, this leads to obtain uniform bonding among reinforcement and matrix.…”
Section: Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…During the solidification process in cast composites, TiB 2 elements cause increase in the dislocation of density [33][34][35][36]. Xuedan Dong et al [10] observed that, when the CeO 2 content was increased, the mechanical properties of the composites were enhanced. Since, Stircasting technique is adopted for the purpose of fabrication of composites, this leads to obtain uniform bonding among reinforcement and matrix.…”
Section: Hardnessmentioning
confidence: 99%
“…But, the wear rate reduced by increasing the TiC content. Xuedan Dong et al [10] studied the effect of CeO 2 particulates on micro-structure and mechanical behavior of Al composites. The outcomes showed that the presence of the suitable wt.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it was reported that the primary precipitates in the structure were Al 4 Cu 9 , Al 2 Cu, and Al 5 Cu 6 Mg 2 phases. [29] Considering that graphene reveals many remarkable properties such as high surface area, high Young's Modulus, and fracture strength, [21,22] FLG-reinforced Al-Si(10 wt%)-Cu (2 wt%)-Mg (1 wt%) composites are estimated to display enhanced mechanical performance. Hence, the effects of FLG content and MA on the microstructural, mechanical, and tribological performances of the Al-10 wt% Si-2 wt% Cu-1 wt% Mg matrix were investigated in this study.…”
Section: Doi: 101002/adem202400046mentioning
confidence: 99%
“…Accordingly, it was reported that the primary precipitates in the structure were Al 4 Cu 9 , Al 2 Cu, and Al 5 Cu 6 Mg 2 phases. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the weight percentage of CeO 2 improved the mechanical characteristics of Al in all composite samples, with porosities reaching their maximum level. The impact of CeO 2 particles on the microstructure and mechanical behaviour of Composite materials was researched by Xuedan Dong [15]. The results demonstrated that the MMCs' tensile strength was enhanced by the appropriate weight percentage of CeO 2 .…”
Section: Introductionmentioning
confidence: 99%